Impregnation of silver in zeolite–chitosan composite: thermal stability and sterility study. (24th May 2019) - Taaca, Kathrina Lois M.; Olegario, Eleanor M.; Vasquez, Magdaleno R.
Abstract: The solvent-casting method was used to synthesize a silver–zeolite–chitosan (AgZ-Ch) composite from Philippine natural zeolites. X-ray diffraction, ultraviolet–visible (UV-Vis) spectroscopy, optical emission spectroscopy (OES), thermogravimetric analysis (TGA) and differential thermogravimetry (DTG) were used to investigate the different properties of the composite before and after plasma treatment. The major phase of the zeolite is Na-clinoptilolite with trace amounts of mordenite, feldspar and quartz. UV-Vis and OES analyses confirmed the presence of Ag and zeolite on the chitosan matrix. The decrease in the transmittance signal at 290 nm and the emission spectra of the discharge showed the presence of Ag I, Al I and Si I signals at 705–852 nm. The TGA and DTG curves revealed the thermal stability of the natural zeolites after ion exchange and after incorporation in the chitosan matrix, where the onset of degradation was observed to occur above ~37°C, the human body temperature. Bacterial count showed minimal growth of colonies on all samples, both pristine and plasma-treated, suggesting that the surface of the composites does not influence bacterial habitation. The fabricated composites meet the minimum requirements for biomedical application such as thermal stability with respect to the average human body temperature and absence of bacteria.